A strategy for combating melanoma with oncogenic c-Myc inhibitors and targeted nanotherapy. (January 2015) - Pan, Dipanjan; Kim, Benjamin; Hu, Grace; Gupta, Deepti Sood; Senpan, Angana; Yang, Xiaoxia; Schmieder, Anne; Swain, Corban; Wickline, Samuel A; Tomasson, Michael H; Lanza, Gregory M
Aims: The activity of the transcription factor c-Myc is dependent upon heterodimerization with Max to control target gene transcription. Small-molecule inhibitors of c-Myc–Max have exhibited low potency and poor water solubility and are therefore unsuitable for in vivo application. We hypothesized that a nanomedicine approach incorporating a cryptic c-Myc inhibitor prodrug could be delivered and enzymatically released in order to effectively inhibit melanoma.Materials & methods: An Sn-2 lipase-labile Myc inhibitor prodrug was synthesized and included in two αv β3 -targeted nanoparticle platforms (20 and 200 nm). The inherent antiproliferate potency was compared with the lipid-free compound using human and mouse melanoma cell lines.Results & conclusion: These data demonstrate for the first time a successful nanodelivery of c-Myc inhibitors and their potential use to prevent melanoma.